ANALISIS KUAT TEKAN BETON MUTU K 200 DENGAN BAHAN CAMPUR FOAMING AGENT, SUPERPLASTICIZER (SIKACIM), DAN FLY ASH - Prandika, Nofvim Eric; Azzahra, Synsya Ealiah; Kristiawan, Agung; Anggi P. S., Putri (Universitas PGRI Semarang, 2025)
Concrete technology innovations need to be made to improve or correct weaknesses and improve the quality standards of the concrete produced. The technology and innovation that has been developed is lightweight concrete. This research aims to find lightweight but high compressive strength concrete (optimal concrete) at K200 concrete grade. With mixed materials for concrete in the form of foam agent, superplasticizer, and fly ash, the tolerance limit for mixing materials at the age of 14 days and 21 days of concrete with experimental methods with cube-shaped samples. Based on the purpose of this study, namely looking for lightweight concrete but high compressive strength (optimal concrete) in this study the average foam 15%, superplasticizer 1.5, fly ash 10% age 14 days with an average of 254.74 kg / cm² and average foam 15% superplasticizer 1.5%, fly ash 10% age 21 days average compressive strength 225.87 kg / cm².